Influence of Habitat, Fire, and Weather on Bobwhite Abundance at Avon Park Air Force Range, Florida - Brett D. Miley; Marian Lichtler (National Quail Symposium Proceedings, 2017)
From 1993 to 2005, we conducted 13 years of early breeding season call counts at Avon Park Air Force Range, in south-central Florida. Historically, this area has been an open, frequently burned landscape with a rainy summer season and a dry spring. We used call count data (n = 67 stations/year) and 400-m buffer areas around each point to investigate the effects of habitat preference, fire impacts, and weather variations on bobwhite abundance. Using logistic regression, we determined that bobwhite in south-central Florida prefer open canopy, dry/mesic habitats in prairie and flatwoods over pine plantations and wet areas. Investigated by ANOVA, bobwhite abundance was highest when at least 40% of a buffer area was burned. Using only burns which occurred on at least 40% of a buffer area, higher bobwhite abundance occurred in buffers which received a dormant or growing season burn within the previous year. Two years post-burn, bobwhite abundance significantly decreased for both burn seasons. Burning in less optimal habitats (e.g., those dominated by dense canopy) did not affect bobwhite populations. Correlation analysis revealed significant negative correlations between bobwhite abundance and April PMDI, May PMDI, and November rain. Bobwhite abundance had significant positive correlations with October PMDI and July rain days. By knowing how local habitat, fire, and weather can impact early breeding season bobwhite abundance, managers may help their population flourish.
Keywords: Colinus virginianus; fire; Florida; habitat; northern bobwhite; weather